Wheat Genetic Resources in Nepal (Nepal Agriculture Research Journal, 2009)
Genetic diversity must be maintained and utilized for sustainable agriculture development. Theamount of genetic diversity in the country depends on the number and diversity of the originalancestors involved in the creation of a germplasm pool, wild relatives and existing landraces.The objective of this research was to study the diversity of wheat gene pool present in theNepalese bread wheat cultivars and landraces that could help for developing conservation andutilization strategy effectively. We examined the pedigrees of 35 Nepalese wheat cultivars andsurveyed the literature for distribution of landraces and wild relatives of wheat. Cultivatedlandraces of spring and winter type, wild landraces and diploid species of wheat are found inNepal. There are 35 improved wheat cultivars, 540 landraces and 10 wild relatives of wheat.Crosses between winter and spring wheat gene pools are far more common and offer a newsource of diversity. Mexico, India and Nepal are the origin countries for 35 cultivars. In Nepalfour cultivars were bred and developed using foreign landraces and maximum number ofcultivars was developed in Mexico. Lerma 52, first improved cereal variety to be released in thehistory of cereal breeding in Nepal was released in 1960. A total of 89 ancestors originated in 22different countries were used to develop these cultivars. Highest number of ancestors was fromIndia. Ancestors of both aestivum and durum species having winter, spring and intermediategrowth habit indicated the collection of wide gene pool. Most of the ancestors were aestivum(76.40%) and spring growth habit (57.31%). Modern varieties are replacing the landraces andimproved old varieties resulted in the genetic erosion. Therefore, in situ, on farm and ex situconservations are necessary for maintaining these genetic variations. Unutilization of locallandraces in breeding program may be the major factor that causes to accelerate the geneticerosion. Gene pool from these landraces along with international gene pool could make towardssuccess in developing high yielding cultivars with wide adaptability. In this study, cultivars andlandraces surveyed represent a wide range of variation for different areas of origin andadaptation.Key words: Ancestor; landrace; origin; wheat gene poolDOI: 10.3126/narj.v7i0.1859Nepal Agriculture Research Journal Vol.7 2006 pp.1-10